Exploring students' needs and perceptions of AI-assisted ESP learning in an english education program context - La Ode Rasmin; Hanafi Pelu; Rosmiati (12 Waiheru, 2026)
This study demonstrates that AI-assisted English for Specific Purposes (ESP) learning addresses gaps in conventional ESP instruction and better supports pre-service English teachers in an English Education Program. Using a qualitative small-scale case study design, the research involved three students from the English Education Study Program in an ESP course at the University of Muslim Buton, Southeast Sulawesi. Data were collected through written semi-structured interviews administered via Google Forms and were analyzed thematically. Students identified ESP as crucial for developing classroom English, instructional communication, and lesson planning skills. However, they found traditional ESP instruction lacked contextual vocabulary and opportunities for independent material development. The integration of AI-supported learning emerged as a practical solution, enhancing students’ understanding of ESP concepts, providing relevant examples, and improving learning efficiency. Students reported increased autonomy and confidence in using English for instruction, while still critically acknowledging risks such as over-reliance on AI and related concerns about academic integrity. They stressed the need for AI to serve as a supportive tool, not a replacement for critical thinking and pedagogical judgment. In summary, the study argues that clearly guided, ethically integrated AI-assisted ESP learning can significantly improve teacher preparation programs.